Synovial Fluid Cell Proteomic Analysis Identifies Upregulation of Alpha-Taxilin Proteins in Rheumatoid Arthritis: A Potential Prognostic Marker - Ashish Sarkar; Shivani Sharma; Prachi Agnihotri; Tanmoy Sarkar; Pooja Kumari; Rajesh Malhotra; Barun Datta; Vijay Kumar; Sagarika Biswas (Journal of Immunology Research)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease affecting the joints and surrounding tissue. Identification of novel proteins associated with the progression of a disease is a prerequisite for understanding the pathogenesis of RA. The present study was undertaken to identify the potential biomarkers from a less explored biological sample such as synovial fluid (SF) cells which is specific for RA and to analyze their functional aspects using proteomic approach. Two-dimensional gel electrophoresis (2-DE) was performed using synovial fluid cells of RA and osteoarthritis (OA) patients, and 7 differentially expressed proteins were identified using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS/MS). Αlpha-Taxilin (α-Taxilin) has been found as one of the novel, significantly up regulated protein in RA. It has been validated in the synovium, synovial fluid (SF), SF cells, and plasma samples by Western blot, enzyme-linked immunosorbent assay (ELISA), fluorescence-activated cell sorting (FACS), immunohistochemistry (IHC), and real-time PCR. The identification of autoantibody against α-Taxilin and in silico studies has further helped us to understand its involvement in disease mechanism. The present study will therefore provide knowledge towards the etiology of RA that pave the way for suitable prognostic marker identification along with other clinical parameters.